inovasi pengajaran akidah dalam meningkatkan keimanan gen-z di era digital - Lailasari, Nadia (Maliki Interdisciplinary Journal, 2025)
Generation Z is a generation born in the midst of globalization and the development of digital technology, where they face serious challenges in maintaining moral and spiritual values. They often experience identity crises and distance themselves from religious teachings because traditional learning methods are considered less relevant to their fast-paced and interactive lives. This article discusses the characteristics of Gen-Z and the challenges they face in understanding and practicing Islamic beliefs, then offers various innovations in teaching methods that suit their characteristics. Teaching strategies such as the use of digital media, interactive learning, contextual approaches, character development, and flexible curriculum are key to forming a more applicable and meaningful understanding of beliefs. Religious education must be designed as a learning experience that touches the spiritual and intellectual side of Gen-Z in a balanced way. Strengthening beliefs through creative and relevant approaches not only aims to increase Islamic knowledge, but also to form character, morality, and critical attitudes needed in real life. The use of inspirational stories and social media as a means of conveying religious messages shows effectiveness in reaching the Gen-Z world. With the right strategy, learning the creed is not only a curricular obligation, but also a foundation in building a strong and relevant Muslim personality amidst the challenges of the digital era.